The Shanghai Alleyway House: A Threatened Typology - Gregory Bracken (Footprint)
The Shanghai alleyway house was a rich and vibrant generator of street life. Unique to Shanghai, it occupied the ambiguous space between the traditional Chinese courtyard home and the street. The system of ‘graduated privacy’ within its alleyways ensured a safe and neighbourly place to live. Due to rapid redevelopment in recent decades this once ubiquitous typology is under threat. This paper takes a look at the history of the typology as well as at three recent redevelopments of it in the city: Xintiandi, Jian Ye Li, and Tianzifang, to question what future there can be for a typology that seems to have outlived its usefulness.